Cerclage wire fixation of trochanteric osteotomies in complex hip revision: our experience and comparison with cable-plate fixation. Issue 5 (September 2022) - Collado, Alicia; Arvinius, Camilla; Serrano, Laura; Otero, Julio; Moro, Enrique; Marco, Fernando
Introduction: Osteotomy of the greater trochanter is a commonly used procedure in complex revision hip arthroplasty in order to achieve a wide exposure to the femoral stem and acetabular components. There is no clinical evidence in favour of a specific fixation method. The aim of this study was to compare cable-plate with figure-of-eight cerclage wire fixation in patients requiring a trochanteric "slide" osteotomy. Material and methods: In a retrospective study, 51 greater trochanteric "slide" osteotomies in complex acetabular revision arthroplasties were included. Patients were divided into 2 groups: 28 hips were fixed with 1 of 2 cable-plate systems (Dall-Miles staple, Stryker or Cable-Ready plate, Zimmer) and 23 with a figure-of-eight cerclage wire. Consolidation, osteolysis, migration of greater trochanter, bursitis of the trochanteric area, Trendelenburg gait and removal of osteosynthesis material were studied at 6 months follow-up. Results: Both groups showed good union rates. The lysis rate was similar with 32% in the cable-plate group versus 29% in the cerclage wire group ( p = 0.084). 43% of the hips with cable-plate and 22% of the cerclage wire had trochanteric migration ( p = 0.297). Pain at the greater trochanter was less frequent in the cerclage wire group (9%) as compared to the cable-plate group (43%) ( p = 0.007). Implant removal was more frequent in the cable-plate group (4 vs. 0 patients). Trendelenburg gait was found in 3 patients in the cerclage wire group as compared to 10 in the cable-plate group ( p = 0.054). Conclusions: The cerclage wiring had superior clinical outcomes with similar radiographic results. The authors recommend the use of figure-of-eight cerclage wire when fixing a greater trochanteric "slide" osteotomy in complex revision hip arthroplasty.